Online Learning in Digital Innovations - Mariono, Andi; Bachri, Bachtiar Syaiful; Kristanto, Andi; Dewi, Utari; Sumarno, Alim; Kholidya, Citra Fitri; Pradana, Hirnanda Dimas (Universitas Pendidikan Ganesha, 2021)
Students and lecturers cannot do direct learning. It is an obstacle in the delivery of material by the lecturer. The purpose of this research is to develop learning in the Digital Learning Learning Media course. This research uses development research—the model development used by ADDIE (Analyze, Design, Development, Implementation, Evaluation). The research subjects are three experts, which include material experts, media experts, learning design experts. The subject of the product trial is students. The methods used to collect data are observation, questionnaires, and tests. The instruments used to collect data are questionnaires and test sheets. The technique used to analyze the data is descriptive qualitative, quantitative, and statistical analysis. The results of the material expert test are 90% with the